Implementation of Cooperatives’ Principles on Ranked-Cooperatives, East Java 2012 - Harwiki, Wiwiek (Journal of Economics and Behavioral Studies, 2014)
The purposes of this research to identify of values and cooperatives’ principles on the field, to identify roles and member participation to improving cooperatives, to identify cooperatives’ performance based on cooperatives’ principles, and to identify problems in order to implementing the cooperatives’ principles. Samples were collected amount 52 cooperatives have been assessed as the accredited cooperatives by Small Medium Enterprise and Cooperatives Office East Java. Methodology supported this research were inventory, field survey, and data analysis. Data have been analyzed and evaluated on 2 steps: grading the defined instrument and checking the supported documents given by respondents. The research findings: Cooperatives’ Principles is an abstract vision which has to spell out how these Principles are to be practiced. The Success programmes as a way to implementing Cooperatives’ Principles that guiding the operation of organization. The product of all cooperatives surveyed was not specific products and need innovation products. Better service for members to survive among other cooperatives. To implement Cooperatives’ Principles, there were correlations between: Management Control and Members’ Satisfaction, Boards’ Performance and Members’ Satisfaction, Well-controlled Administration and Members’ Satisfaction, Capital Structure and Members’ Satisfaction, Unit Business and Members’ Satisfaction, Training & Education and Members’ Satisfaction, Cohesiveness and Members’ Satisfaction.